NTP Regeneration and its Application in the Biosynthesis of Nucleotides and their Derivatives - Ding, Qingbao; Ou, Ling (Current Pharmaceutical Design, 2017)
Background: Nucleoside 5'-triphosphates (NTPs) play an important role in cells in the transfer of phosphate groups or bioenergy. In vivo, they are ready to be produced, regenerated and consumed in different kinds of metabolic pathways, and their concentrations are strictly controlled. NTPs are useful reagents that take part in many biosynthetic processes. However, NTPs are expensive and unstable, which greatly increases the cost of the final product if a large amount of NTPs is used directly in biosynthesis. Furthermore, during reactions, NTPs degrade into NDPs and need to be separated from the reaction mixture, making the operation complicated. Therefore, NTPs are normally regenerated from NDPs, and only very few NTPs are used in the reaction. Method: Mechanisms of NTP regeneration were analysed, and their applications in the biosynthesis of nucleotides and their derivates were described. Basically, NTP regeneration involves isolated enzyme systems and whole-cell systems. Result: As one type of cofactor regeneration, NTPs can be effectively regenerated by acetate kinase, pyruvate kinase, and polyphosphate kinase from acetyl phosphate, phosphoenol pyruvate, and polyphosphate, respectively, or by whole cells of yeast and Corynebacterium ammoniagenes from simple carbohydrates and phosphate. The NTP-regeneration method is selected primarily due to the main reaction that it is being coupled with. The cost of phosphate donors and the convenience of integration with the main process should be considered. Conclusion: Significant advances have been made when NTP regeneration is coupled with other biosynthetic processes, especially in the preparation of nucleotides, 2'-deoxynucleotides, sugar-nucleotides and their derivatives.
Keywords: polyphosphate kinase